2020
DOI: 10.1136/gutjnl-2019-319954
|View full text |Cite
|
Sign up to set email alerts
|

Seven-day vonoprazan and low-dose amoxicillin dual therapy as first-lineHelicobacter pyloritreatment: a multicentre randomised trial in Japan

Abstract: ObjectiveTo date, no randomised trials have compared the efficacy of vonoprazan and amoxicillin dual therapy with other standard regimens for Helicobacter pylori treatment. This study aimed to investigate the efficacy of the 7-day vonoprazan and low-dose amoxicillin dual therapy as a first-line H. pylori treatment, and compared this with vonoprazan-based triple therapy.DesignThis prospective, randomised clinical trial was performed at seven Japanese institutions. Patients with H. pylori–positive culture test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
237
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(275 citation statements)
references
References 46 publications
7
237
0
2
Order By: Relevance
“…This is likely due to use of vonoprazan as a substitute for PPIs, which reportedly enhances the therapeutic efficacy of CLR‐ and STFX‐based H pylori eradication regimens by increasing gastric pH 33‐35 . Recent reports utilizing vonoprazan in dual therapy with AMX also showed very high eradication rate in the first‐line therapy, suggesting the unnecessity of second antibiotic 36,37 . Thus, sufficient acid suppression achieved by vonoprazan would be one of important factors for successful eradication of refractory H pylori 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to use of vonoprazan as a substitute for PPIs, which reportedly enhances the therapeutic efficacy of CLR‐ and STFX‐based H pylori eradication regimens by increasing gastric pH 33‐35 . Recent reports utilizing vonoprazan in dual therapy with AMX also showed very high eradication rate in the first‐line therapy, suggesting the unnecessity of second antibiotic 36,37 . Thus, sufficient acid suppression achieved by vonoprazan would be one of important factors for successful eradication of refractory H pylori 38 .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Alternatives to triple eradication therapy include bismuth quadruple therapy, concomitant therapy, sequential therapy, 4 and recently introduced vonoprazan therapy. 58,59 While concomitant and bismuth quadruple therapy have showed longterm perturbations of the gut microbiome, 47 vonoprazan therapy supplemented by probiotics has been shown to improve the rate of eradication and potentially aids the maintainment of species diversity within the gut microbiome. 60 Although a number of studies have identified vonoprazan as effective eradication strategy, [59][60][61] study evaluating the effect of vonoprazan monotherapy on the gut microbiome revealed stimulated lipopolysaccharide biosynthesis thus increasing the risk of enteric infection.…”
Section: Influence Of Eradication Therapy On the Gut Microbiomementioning
confidence: 99%
“…58,59 While concomitant and bismuth quadruple therapy have showed longterm perturbations of the gut microbiome, 47 vonoprazan therapy supplemented by probiotics has been shown to improve the rate of eradication and potentially aids the maintainment of species diversity within the gut microbiome. 60 Although a number of studies have identified vonoprazan as effective eradication strategy, [59][60][61] study evaluating the effect of vonoprazan monotherapy on the gut microbiome revealed stimulated lipopolysaccharide biosynthesis thus increasing the risk of enteric infection. 62 In general, adverse events are common in combinatorial therapies, thereof vonoprazan therapy accompanied by probiotics might be promising strategy in H pylori eradication, especially in regions with high resistance rates to clarithromycin.…”
Section: Influence Of Eradication Therapy On the Gut Microbiomementioning
confidence: 99%
“…The eradication rates attained by a proton pump inhibitor (PPI), amoxicillin and clarithromycin were reportedly very low in patients infected with clarithromycin-resistant strains of H. pylori ,5 6 although amoxicillin-resistant strains of H. pylori are rare in Japan. The present study by Suzuki et al 1 accounts for the poor eradication rates by the triple therapy with a PPI, amoxicillin and clarithromycin in patients infected with clarithromycin-resistant strains of H. pylori . These clinical studies have suggested that clarithromycin not only does not work as antibiotics, but also has an adverse effect on the action of other antibiotics in cases infected with clarithromycin-resistant strains of H. pylori .…”
mentioning
confidence: 81%
“…We read the manuscript written by Suzuki et al 1 with interest. They reported that the eradication rate of Helicobacter pylori attained by the dual therapy with vonoprazan and amoxicillin (VA-Dual) was almost the same as that attained by the triple therapy with vonoprazan, amoxicillin and clarithromycin (VAC-Triple), as previously reported by us 2.…”
mentioning
confidence: 99%